2018
DOI: 10.1093/mmy/myy078
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal injection of Pythium insidiosum protein antigens for improved diagnosis and treatment of pythiosis in an experimental model

Abstract: The oomycetous pathogen Pythium insidiosum is the causative agent of pythiosis, a life-threatening disease that affects animals and humans. This infectious disease is difficult to treat, and early and accurate diagnosis is critical for effective treatment. In this sense, this study aimed to evaluate the intradermal (ID) injection of P. insidiosum protein antigens (PiPA) for the diagnosis and treatment of pythiosis using an experimental model. For diagnostic purposes, PiPA were injected by the ID route in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Nevertheless, the intradermal test using a 0.2mL dosage via ID was as effective as the subcutaneous route for treating pythiosis in horses. These findings are consistent with experiments conducted by Weiblen et al (2019), which demonstrated that treatment effectiveness and cure rates did not differ significantly between intradermal and subcutaneous routes in treating experimentally induced pythiosis in rabbits. In addition, combining immunotherapy via ID with triamcinolone acetonide showed promising results in treating infected animals.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the intradermal test using a 0.2mL dosage via ID was as effective as the subcutaneous route for treating pythiosis in horses. These findings are consistent with experiments conducted by Weiblen et al (2019), which demonstrated that treatment effectiveness and cure rates did not differ significantly between intradermal and subcutaneous routes in treating experimentally induced pythiosis in rabbits. In addition, combining immunotherapy via ID with triamcinolone acetonide showed promising results in treating infected animals.…”
Section: Discussionsupporting
confidence: 91%
“…An APC should process an immunomodulating antigen of P. insidiosum, such as (1,3)(1,6)-β-glucan, which is a main cell wall component [251,253,254], before priming a resulting antigenic epitope to a naïve T cell (via MHC-TCR complex) [242,243]. This cellular interaction might trigger the release of IFNγ and IL-2 for enhancing the differentiation of Th0 to Th1 cell and Th0 to regulatory T (Treg) cell, respectively [242,246,251,252,255,256]. The Th1 cell produces IFN-γ to activate the macrophages and cytotoxic T lymphocytes [131,142,242,244,246,251,253,256].…”
Section: Proposed Mechanism Of P Insidiosum Antigen-based Immunotherapymentioning
confidence: 99%
“…Therefore, a multicentric prospective clinical study should be performed to gain insights into the pharmacologic properties of PIA, such as efficacy, adverse effect, optimal dose, and antigen administration. The rabbit model of pythiosis has been established to investigate PIA immunotherapeutic properties [122,250,255,261]. Such an animal model shows atypical manifestations (i.e., cutaneous nodules) compared with pythiosis in the natural hosts (i.e., humans and various animals) [50,97,122,216,224,[262][263][264].…”
Section: Future Perspectivementioning
confidence: 99%